Neutrophils - to - Lymphocytes Ratio and Clinical Outcomes in Patients with Kidney Diseases in COVID 19 - Sharma, Deepak; Upadhyay, Hari Prasad; Sharma, Taranath; Ghimire, Madhav; Aryal, Bandana; Kakshapati, Mira (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: Kidney Disease is structural and functional abnormality of Nephrons, where abrupt deterioration to progressive decline in Kidney function leads to acute to chronic Kidney Disease, respectively. The objective of this research was to find the Neutrophil-to-Lymphocyte ratio and Clinical outcomes of patients with Kidney Diseases in COVID-19. Methods: A descriptive cross-sectional study was conducted in the Department of Nephrology of College of Medical Sciences and Teaching Hospital, Bharatpur-10, Chitwan from 2021-04-01 to 2021-06-29 in among 31 Covid-19 positive cases. Collected data was entered and analyzed by using SPSS 20. Results: In this study 58% were male while 42% were female. Among the total cases 35.48% cases had NRL ratio <8 while 65.52% cases had NRL ratio ≥8. Among total cases 48.38% were discharged whereas, 51.62% were declared dead. Also, among those cases whose NRL ratio <8, 27.27%were declared dead while in NRL≥8, 65% cases were declared dead during treatment. Conclusions: In Covid-19 cases early diagnosis and supportiv e treatment, prognosis could be good. Regular follow-up could give insight about kidney function whereas in case Covid-19 various awareness programme and practice to prevent should be implied.